The process of market integration European securities (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
There is an on-going debate regarding the integration process Europe is undergoingin its financial markets and, more specifically, its Stock Exchanges. Along with other pressing issues, it is centered around the impact that this consolidation process will have on trading costs for shares being quoted in these Stock Exchanges. This will,hence, have a direct effect on these firms’ financial costs and sooner or later will even play a role in the overall growth of the European economy.This essay is aimed at contributing several conclusions related to the theoretical discussion about whether this Stock Exchange consolidation process will or will nothave any real effect on trading costs. An Econometric Analysis Process has beenused, and, more specifically, a series of techniques to correct imbalances so as to verify the hypothesis that states that the variable referring to the size of any given StockMarket. This theory states that the larger the Market, the lower its trading costs. Inother words, we have tried to verify if the variable relating to the size of a StockExchange and its trading costs do maintain a long term, well-balanced relationshipand if the former may be an efficient measuring stick for calculating the latter. This essay develops an Empirical research project based upon a real case, the Euronext Stock Market (this alliance was created in 2000 as the merger of three Stock Exchanges, those in Amsterdam, Brussels and Paris). To carry out this research project, 78 companies were chosen that had been quoted in the main markets involved in this alliance in 1999 (hence before the integration) and were still being quotedin 2003 (hence after the integration). An econometric model with the properparameters was produced to measure the lowering of their trading costs in these marketsthat were directly due to the consolidation process. Once this step had beenfinished, we studied the usefulness of this model as a tool for measuring and forecastingfuture scenarios for the main European Stock Markets. In this way, we haveshown that there is indeed an indirect relationship between the size of a Stock marketand its trading costs and a series of hypothesis have been seen to be true, provingthat further reductions related to these costs will be attained through future integrationprocesses among the main European Stock Exchanges.It is our hope that the conclusions that have been reached will be useful for theManagers of these Markets as they design their future strategies.
Keywords: Financial markets; financial integration; Europe; Stock Exchanges; trading costs; bid-ask spreads; Euronext